Les prairies de l’estuaire de la Loire : étude de la dynamique de la végétation de 1982 à 2014 - Mathieu Le Dez; Jérôme Sawtschuk; Frédéric Bioret (M@ppemonde)
This article presents the diachronic analysis of vegetation maps to characterize vegetation dynamics of Loire estuary at diﬀerent spatial and temporal scales. A transition matrix model was applied to quantitatively describe the dynamic processes observed. Analyses reveal the regression of meadows, the development of reed beds, woodlands, and halophytes. These results can be related to changes in land use and hydro-sedimentary modiﬁcations of the estuary.